2014
DOI: 10.3390/ijms151223418
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in β-Cell Differentiation of Pluripotent Stem Cells Induced by Small and Large Molecules

Abstract: Human pluripotent stem cells, including human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs), hold promise as novel therapeutic tools for diabetes treatment because of their self-renewal capacity and ability to differentiate into beta (β)-cells. Small and large molecules play important roles in each stage of β-cell differentiation from both hESCs and hiPSCs. The small and large molecules that are described in this review have significantly advanced efforts to cure diabetic disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 182 publications
(264 reference statements)
0
25
0
1
Order By: Relevance
“…In published stem cell differentiation protocols, soluble molecules are added in different concentrations at different time points to mimic the stepwise embryonic development. [ 43 ] Likewise, the physical microenvironment changes during embryonic development, [ 44 ] and hereby the different differentiation steps may require different physical environments. Further the expression of the mechanical cell receptors integrins changes during stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…In published stem cell differentiation protocols, soluble molecules are added in different concentrations at different time points to mimic the stepwise embryonic development. [ 43 ] Likewise, the physical microenvironment changes during embryonic development, [ 44 ] and hereby the different differentiation steps may require different physical environments. Further the expression of the mechanical cell receptors integrins changes during stem cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Postnatal development of pancreatic beta-cells has become an important subject of research in recent years not only for the achievement of the capability to differentiate progenitor or reprogramed cells into insulin-secreting cells (Mayhew & Wells 2010, Schroeder 2012, Kumar et al 2014) but also to control beta-cell proliferation and maturation as a therapeutic approach in diabetes. Earlier work has suggested that cells that produce and secrete insulin can be generated using a variety of strategies (Sena et al 2010, Vetere et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…To explore induction further, we supplemented the culture medium with additional molecules to improve their maturation: GLP‐1, exendin‐4, and betacellulin. GLP‐1 was incorporated at Stage 3 of our original protocol to promote IPC maturation, whereas exendin‐4 and betacellulin have been widely used to promote the maturation and differentiation of MSCs into functional pancreatic cells (Kumar et al, ; Li, Lam, Xu, Lam, & Chung, ; Wong, ).…”
Section: Resultsmentioning
confidence: 99%